The Concept of Cinema Freedom - Alesheikh, Rahim; Abbasi, Bizhan; Gorji, Aliakbar (Journal of History Culture and Art Research, 2018)
In this paper, the concept of cinema freedom is explained, and its comprehensive definition is presented within the limitations on the form and essence. First, based on these definitions, the dimensions of cinema freedom which include the freedom of screening and expression and freedom of work are depicted. The question of “what is cinema freedom?” is examined by implementing descriptive-analytical methods. The cinema freedom is defined as when each person or group is able to publish a cinematic artwork with any thoughts or beliefs. Based on the restrictions of freedom of screening and expression and freedom of work, the limits of cinema freedom are categorized into form and essence limitations. It should be noticed that different countries are applying these limitations in different ways.